THE PERCEPTION OF WORKERS ABOUT SELF-CARE WITH LUMBAR SPINE - Farias, Luana Maria (2023)
To analyze the perception of workers about self-care with the lumbar spine. Qualitative intervention study, conducted in a Basic Health Unit in Guaiúba, Ceará. An active search was conducted with patients complaining of low back pain. These patients were invited to participate in four health education meetings, and at the last meeting a focus group was held. It was identified that after the meetings, the participants obtained positive changes in behavior related to lumbar care. Eight women participated. In the reports, aspects of the behavior of the participants that interfere in health care were identified, as observed in the categories presented: practice of physical exercise in pain relief; care with the day-to-day posture and the physiotherapist's performance in health promotion. The participants were aware of the importance of self-care with the spine, adhering to the daily practice of strengthening the lumbar spine.